Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1136/ard.56.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of steroid placement with clinical outcome in patients with shoulder symptoms

Abstract: Objective-To study the eVect of accuracy on the clinical outcome of local steroid injections to the shoulder. Methods-37 patients with shoulder symptoms of at least two months' duration received local injections of a mixture of triamcinolone and radiographic contrast material using a standardised technique. Radiographs of the joint were taken immediately afterwards. Details of the patients' symptoms (assessed by visual analogue scales) and range of movement at the joint were obtained before and two weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(163 citation statements)
references
References 11 publications
(3 reference statements)
3
142
2
3
Order By: Relevance
“…This is now a relevant issue for physiotherapists as many working in an extended scope role in the NHS are now performing injections. It has been documented that 14-71% of injections carried out ''blind''-without image guidance-miss their target [23][24][25][26][27]. What we do not know is whether this makes a difference in clinical efficacy.…”
Section: Ultrasound-guided Injectionsmentioning
confidence: 86%
See 1 more Smart Citation
“…This is now a relevant issue for physiotherapists as many working in an extended scope role in the NHS are now performing injections. It has been documented that 14-71% of injections carried out ''blind''-without image guidance-miss their target [23][24][25][26][27]. What we do not know is whether this makes a difference in clinical efficacy.…”
Section: Ultrasound-guided Injectionsmentioning
confidence: 86%
“…It is perhaps because of these concerns and the improved technology that ultrasound is an increasingly popular technique to ensure accuracy of softtissue injection in sports medicine for medical staff and physiotherapists [28]. Eustace et al [24] report improved outcomes in shoulder pain in accurately placed subacromial and glenohumeral injections. Nevertheless, some have suggested that ultrasound guidance does not make a difference in long-term efficacy [29,30].…”
Section: Ultrasound-guided Injectionsmentioning
confidence: 99%
“…5,9,[12][13][14]46 One reason for such differences possibly can be related to variability in the accuracy of injected corticosteroid placement. For example, the success rate of blinded subacromial injection varied greatly from 29% to 83% depending on injection methods and operators, [47][48][49][50] with better treatment effect from corticosteroids more accurately injected into the subacromial bursa. 9,15,51 With recent advances in diagnostic ultrasound in musculoskeletal medicine, ultrasound-guided injections have become prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that ultrasound enables a more accurate delivery of the pharmacological agent at the correct anatomical site. Blind subacromial injections are intrabursal in only 7-29% of cases [2][3][4][5]. However, the impact on therapeutic effect is controversial.…”
Section: Image Guidancementioning
confidence: 99%
“…External impingement of the shoulder associated with subacromial bursitis may be effectively treated by intrabursal injection of steroid and anaesthetic [2]. It is common practice to use volumes of at least 10 ml to fill the bursa in an attempt to break down bursal adhesions.…”
Section: Bursitis and Impingement Syndromesmentioning
confidence: 99%